Androgen alleviates neurotoxicity of β‐amyloid peptide (Aβ) by promoting microglial clearance of Aβ and inhibiting microglial inflammatory response to Aβ. (20th September 2017) - Yao, Peng‐Le; Zhuo, Shu; Mei, Hong; Chen, Xiao‐Fang; Li, Na; Zhu, Teng‐Fei; Chen, Shi‐Ting; Wang, Ji‐Ming; Hou, Rui‐Xing; Le, Ying‐Ying
Summary: Aims: Lower androgen level in elderly men is a risk factor of Alzheimer's disease (AD). It has been reported that androgen reduces amyloid peptides (Aβ) production and increases Aβ degradation by neurons. Activated microglia are involved in AD by either clearing Aβ deposits through uptake of Aβ or releasing cytotoxic substances and pro‐inflammatory cytokines. Here, we investigated the effect of androgen on Aβ uptake and clearance and Aβ‐induced inflammatory response in microglia, on neuronal death induced by Aβ‐activated microglia, and explored underlying mechanisms. Methods: Intracellular and extracellular Aβ were examined by immunofluorescence staining and Western blot. Amyloid peptides (Aβ) receptors, Aβ degrading enzymes, and pro‐inflammatory cytokines were detected by RT‐PCR, real‐time PCR, and ELISA. Phosphorylation of MAP kinases and NF‐κB was examined by Western blot. Results: We found that physiological concentrations of androgen enhanced Aβ42 uptake and clearance, suppressed Aβ42 ‐induced IL‐1β and TNFα expression by murine microglia cell line N9 and primary microglia, and alleviated neuronal death induced by Aβ42 ‐activated microglia. Androgen administration also reduced Aβ42 ‐induced IL‐1β expression and neuronal death in murine hippocampus. Mechanistic studies revealed that androgen promoted microglia to phagocytose and degrade Aβ42 through upregulating formyl peptide receptor 2 and endothelin‐converting enzyme 1c expression, and inhibited Aβ42 ‐induced pro‐inflammatory cytokines expression via suppressing MAPK p38 and NF‐κB activation by Aβ42, in an androgen receptor independent manner. Conclusion: Our study demonstrates that androgen promotes microglia to phagocytose and clear Aβ42 and inhibits Aβ42 ‐induced inflammatory response, which may play an important role in reducing the neurotoxicity of Aβ.